Effects of spirulina supplementation alone or with exercise on cardiometabolic health in overweight and obese adults: a systematic review and meta-analysis - Fu, Zhenliang; Zhou, Shibiao; Gu, Xueyan (Frontiers in Nutrition, 2025)
PurposeThis systematic review and meta-analysis evaluates the effects of Spirulina supplementation, alone or combined with exercise, on body composition, lipid profiles, glycemic control, blood pressure, and cardiorespiratory health in overweight and obese adults. It also examines the moderating roles of participant characteristics and intervention protocols.MethodsWe systematically searched PubMed, Embase, Cochrane Library, and Web of Science from their inception to September 2024. Results were pooled using random-effects models and reported as Hedge’s g (g) with 95% confidence intervals (95% CI). Heterogeneity was explored through subgroup and regression analyses. Bias risk and evidence quality were assessed using the Cochrane RoB 2 tool and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach.ResultsTwenty-three studies (1,035 participants) were included. Spirulina supplementation alone significantly reduced body weight (g = −0.30, 95% CI: −0.53 to −0.08), total cholesterol (g = −0.79, 95% CI: −1.18 to −0.41), triglycerides (g = −0.64, 95% CI: −1.00 to −0.28), low-density lipoprotein cholesterol (LDL-C; g = −0.71, 95% CI: −1.13 to −0.29), and diastolic blood pressure (g = −0.73, 95% CI: −1.43 to −0.03), while increasing high-density lipoprotein cholesterol (HDL-C; g = 0.53, 95% CI: 0.04 to 1.02). When combined with exercise, Spirulina further improved HDL-C (g = 1.08, 95% CI: 0.37 to 1.79) and LDL-C (g = −0.81, 95% CI: −1.59 to −0.04). Subgroup and regression analyses revealed that participant age, body mass index, health status, Spirulina form, dosage, and intervention duration influenced outcomes.ConclusionSpirulina may serve as a valuable adjunctive therapy for overweight and obese individuals with metabolic disorders, reducing cardiovascular risk by improving lipid profiles, blood pressure, and body weight. Combining Spirulina with exercise enhances certain lipid outcomes. However, its overall impact on body composition and glycemic control appears limited. Further research is needed to confirm its long-term efficacy.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024573534, identifier CRD42024573534.